Analisis Model Pembelajaran Problem Based Learning (PBL) sebagai Peningkatan Minat Belajar Peserta Didik terhadap Pembelajaran PPKn di Sekolah Dasar - Apriwati, Resi (Al-DYAS, 2024)
Education plays a very important role in efforts to improve Human Resources (HR). One of the main factors of important activities in the educational process is learning. Interest in learning is an urge that comes from within the student himself to learn, so a feeling of interest arises which ends with a decision to learn within him. Where students have an interest in learning, these children tend to feel happy and interested in learning. Basically, choosing a learning model has a significant effect on increasing students' interest in learning, especially in Civics learning in elementary schools. The relevance of the learning model applied means that students' interest in learning in a class increases. One learning model that attracts students' interest is the Problem Based Learning (PBL) Learning Model. This learning model is related to the way students are active in learning.